Criminal Punishment for The Dissemination of False Information Causing Public Panic Under The Criminal Code (KUHP) - Raffi Rizkytia Novebryan; Wahyuningrum W; Siti Ahdia Fawwaz Nurwendha; Yamin Y (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The dissemination of false information or hoaxes that cause public panic constitutes a serious challenge in modern society, particularly in the digital era characterized by rapid information flow and minimal verification processes. The massive spread of false information can generate social unrest, disrupt public order, and potentially threaten national stability as well as public trust in the state. Therefore, criminal law plays a crucial role as an instrument for protecting public interests through regulation and punishment of such acts. This article aims to analyze the regulation of criminal sanctions against the dissemination of false information that causes public panic within the National Criminal Code (KUHP), especially following the enactment of the 2023 KUHP. This research employs a normative juridical method with statutory and conceptual approaches by examining criminal law norms, legal doctrines, and relevant regulations. The findings indicate that the regulation of false information dissemination in the new KUHP reflects the state's effort to maintain public order and provide legal certainty, yet it requires careful interpretation to avoid conflict with the principle of freedom of expression. Thus, criminal punishment for the dissemination of false information must be applied proportionally, fairly, and oriented toward the protection of public interests.